Hydrothermal Synthesis of Multifunctional Polyvinyl Alcohol-based Nanocomposites Reinforced with Biosynthesized Silver Nanoparticles: Enhanced Thermal, Dielectric, and Biological Performance - Erol, Ibrahim; Gursoy, Oznur; Khamidov, Gofur; Hazman, Omer; Yakuphanoğlu, Fahrettin (Springer, 2025)
This study focused on the preparation of novel multifunctional polyvinyl alcohol (PVA)-based nanocomposites and the determination of their versatile properties. The nanocomposites contain a blend of PVA and a polystyrene-derived polymer (polymethyl-4-[(4-ethenylphenyl)methoxy]benzoate) (PMST), and biosynthesized silver nanoparticles (AgNPs). The hydrothermal interaction of PVA and PMST resulted in good compatibility and was confirmed by the single glass transition temperature (Tg) value obtained from DSC. The characterization of the nanocomposites produced by incorporating biogenic AgNPs with an average size of 26 nm produced with Verbascum nudatum var extract was carried out by SEM-EDX, TEM, XRD, and FTIR. SEM-EDX data confirmed that AgNPs exhibited a good dispersion. The thermal decomposition temperature of PVA, 260 degrees C, increased to 318 degrees C with the addition of 7% AgNPs. The same situation was also seen in Tg values. The nanocomposites' determined water contact angle values showed that AgNPs reduced hydrophilicity. The water contact angle value of PVA, which was 53.40o, increased to 74.61o with the addition of AgNPs. It was observed that with the increased AgNP concentration added to the PVA-PMST blend, the alternating current (AC) conductivity increased to 2.61 x 10(- 6) S/cm, and the frequency-dependent dielectric constant decreased to 2.42. It was observed that the determined antioxidant values of the nanocomposites improved with the addition of AgNPs. In addition, it was determined that the nanocomposites exhibited an effect close to the reference antibiotic with an inhibition diameter of 14 mm against the E. coli pathogen at the highest AgNP loading rate. The multifunctional properties of the nanocomposites produced by the hydrothermal method indicate that they can be used in food, electronics, and biomedical fields.
Keywords: PVA; Polystyrene; Silver nanoparticle; Antimicrobial effect; Dielectric properties